A Time-Space Analysis of Urban Activities with Focus on the Relationship between ICT and Activity-Travel - Kuniaki Sasaki; Kazuo Nishii; Ryuichi Kitamura; Katsunao Kondo (European Regional Science Association (ERSA), 2005)
Information and communications technology (ICT) has evolved substantially and impacted urban residents' everyday life quite substantially in the past decade. The rapid spread of mobile telecommunications technologies has produced significant changes in relationships among communications, marketing and distribution, and transportation. As mobile technologies diminish time-space constraints that have governed telecommunication, they are prompting the emergence of new life styles with unprecedented ways in which urban space is consumed. The focus of this study is on how mobile telecommunication technologies have influenced daily activity and travel behaviors of urban residents. Temporal and spatial characteristics of their activity-travel patterns are empirically analyzed using activity diary data sets collected by the authors in the Kofu area of Japan. The survey is designed with the intent of capturing both patterns of movements in the urban area and patterns of activities that induced the movements. Questions regarding telecommunications activities are introduced into the activity-travel diary that had been developed by the authors to facilitate the acquisition of information on the occurrence and contents of telecommunications activities. The analytical framework of this study is formed by integrating urban residents' time-space paths and virtual links representing telecommunications activities. Time-space paths are formed in a physical urban space while satisfying temporal and spatial constraints imposed by Hägerstrand's prism. Conventional means of inter-individual communication (meeting, stationary telephones, mailed letters and telegrams) are all subject to certain constraints in the time-space domain. On the other hand, telecommunications activities by mobile technologies are not subjected to many of the constraints and can influence travel decisions more spontaneously than do conventional means of communication. Several hypotheses concerning ICT and activity patterns are postulated and empirically examined with the results of the diary surveys. Examples of the hypotheses are as follows. As the use of mobile telecommunications technologies increases, 1) the activity frequency tends to increase, 2) the spatial distribution of activities tends to spread out, that is, the action space tends to expand spatially, and 3) patterns of trip chaining tend to change themselves, with more stops incorporated into a home-based trip chain (i.e., a sequence of trips starting from and ending at home, through which a set of activity locations are visited). It is also hypothesized that 4) the way mobile technologies influence the individual's activity-travel patterns varies by his personal characteristics, especially life cycle stage and life style. The Survey of Communication, Activity and Travel, denoted by "SCAT,” was conducted twice to form the database of this study. The first survey involved about 150 university students and data on weekly activity patterns and mobile telecommunication incidents were collected. The second survey addressed about 150 households (322 individuals) and activity diaries on two consecutive days and mobile telecommunication information were obtained. The first SCAT data are used to examine basic properties of ICT–activity-travel relationships of "heavy mobile-informed travelers” because students are certainly standing on the forefront of ICT use. On the other hand, the second SCAT data are used to analyze characteristics of joint activity engagement by household members as a result of ICT use among household members. Then, using both of the SCAT data sets, the hypotheses are examined and statistical evidence is presented. Finally, implications of the findings are summarized and directions are suggested for future research on ICT, activity and travel.
Keywords: 330